Optical clumped isotope thermometry of carbon dioxide - Prokhorov, Ivan; Kluge, Tobias; Janssen, Christof (Scientific reports, 2019)
Simultaneous analysis of carbon dioxide isotopologues involved in the isotope exchange between the doubly substituted 13C16O18O molecule and 12C16O2 has become an exciting new tool for geochemical, atmospheric and paleoclimatic research with applications ranging from stratospheric chemistry to carbonate-based geothermometry studies. Full exploitation of this isotope proxy and thermometer is limited due to time consuming and costly analysis using mass spectrometric instrumentation. Here, we present an all optical clumped CO2 isotopologue thermometer with capability for rapid analysis and simplified sample preparation. The current development also provides the option for analysis of additional multiply-substituted isotopologues, such as 12C18O2. Since the instrument unambiguously measures all isotopologues of the 12C16O2 + 13C16O18O  - - - - $$\rightleftharpoons $$ - - - ⇌ - - -  13C16O2 + 12C16O18O exchange, its equilibrium constant and the corresponding temperature are measured directly. Being essentially independent of the isotope composition of the calibration gas, an uncalibrated working reference is sufficient and usage of international calibration standards is obsolete. Other isotopologues and molecules can be accessed using the methodology, opening up new avenues in isotope research. Here we demonstrate the high-precision performance of the instrument with first gas temperature measurements of carbon dioxide samples from geothermal sources.
Gesehen am 08.04.2019